Consumption of Sugar Added Drinks Among Students in Malaysia - Tong, Hui Lee; Cheah, Yong Kang (Journal of Business Management and Accounting, 2025)
Sugar added drinks are harmful to health. People are likely to suffer from chronic diseases if they consume sugar added drinks regularly. The objective of this study is to investigate the relationships between consumption of sugar added drinks and demographic, lifestyle and parental factors among university students in Malaysia. To the best of our knowledge, there is still a lack of in-depth studies that focus on this topic in Malaysia. Primary data used in this study were obtained from a cross-sectional survey. A total of 400 students from the Universiti Utara Malaysia were surveyed. A negative binomial regression model was applied to generate important findings. Findings from this study showed that students’ monthly consumption of sugar added drinks had significant associations with numerous demographic, lifestyle and parental factors. In particular, students were more likely to consume sugar added drinks if they were younger, were Malays, had less-educated parents, used e-cigarettes and were less physically active. In conclusion, age, ethnicity, use of e-cigarettes, physical activity and parental education levels play an important role in determining added sugar intake in the student population. These findings can assist policymakers in formulating a more effective measure directed towards reducing sugar added drink intake among university students.
Keywords: consumption; demographic factors; parents; sugar added drinks; students